(untitled) (Al-Aasar, 2025)
Supplication is an important worship. Its importance is emphasized in Islam. It is a means of communication between the man and Allah. The Holy Quran mentions various supplications of prophets and righteous people in different styles. These supplications include the different effects. Sometimes they are complaints, sometimes they are expressions of gratitude, sometimes they are reminders, sometimes they are claims against someone and sometimes they are mentions of reporting after fulfilling one’s responsibility. It also mentions the supplications of Satan in which he seeks respite from misleading the believers until the Day of Judgment. These supplications include the names of Allah and other attributes of Allah. We also need to include this most beautiful style of the Quran in our supplications so that our prayers can be effective.